The subthalamic microlesion story in Parkinson's disease: electrode insertion-related motor improvement with relative cortico-subcortical hypoactivation in fMRI. - Robert Jech; Karsten Mueller; Dušan Urgošík; Tomáš Sieger; Štefan Holiga; Filip Růžička; Petr Dušek; Petra Havránková; Josef Vymazal; Evžen Růžička (PLoS ONE)
Electrode implantation into the subthalamic nucleus for deep brain stimulation in Parkinson's disease (PD) is associated with a temporary motor improvement occurring prior to neurostimulation. We studied this phenomenon by functional magnetic resonance imaging (fMRI) when considering the Unified Parkinson's Disease Rating Scale (UPDRS-III) and collateral oedema. Twelve patients with PD (age 55.9± (SD)6.8 years, PD duration 9-15 years) underwent bilateral electrode implantation into the subthalamic nucleus. The fMRI was carried out after an overnight withdrawal of levodopa (OFF condition): (i) before and (ii) within three days after surgery in absence of neurostimulation. The motor task involved visually triggered finger tapping. The OFF/UPDRS-III score dropped from 33.8±8.7 before to 23.3±4.8 after the surgery (p<0.001), correlating with the postoperative oedema score (p<0.05). During the motor task, bilateral activation of the thalamus and basal ganglia, motor cortex and insula were preoperatively higher than after surgery (p<0.001). The results became more enhanced after compensation for the oedema and UPDRS-III scores. In addition, the rigidity and axial symptoms score correlated inversely with activation of the putamen and globus pallidus (p<0.0001). One month later, the OFF/UPDRS-III score had returned to the preoperative level (35.8±7.0, p = 0.4).In conclusion, motor improvement induced by insertion of an inactive electrode into the subthalamic nucleus caused an acute microlesion which was at least partially related to the collateral oedema and associated with extensive impact on the motor network. This was postoperatively manifested as lowered movement-related activation at the cortical and subcortical levels and differed from the known effects of neurostimulation or levodopa. The motor system finally adapted to the microlesion within one month as suggested by loss of motor improvement and good efficacy of deep brain stimulation.